Violencia obstétrica: aspectos históricos - Gutiérrez-Ramos, Miguel (2024)
From ancient times to the present day, pregnancy and childbirth are one and thesame biological process. What has changed is the environment and the way oursociety has cared for them. Modern medicine and technology have prevented manycomplications of pregnancy, childbirth and the postpartum period and saved manylives, but the woman-centered approach has been neglected. It is not a matter ofgoing totally back to the past and leaving modern childbirth care aside to avoid themisnamed 'obstetric violence'. Rather, it is about incorporating what was valuable inpast care, such as the involvement of the family, of the couple. But also, the respectof ethical principles, the quality of care for a safe delivery, as well as the rights ofthe pregnant woman so that obstetric care is a modern and humanized care, as allwomen deserve.